2022
DOI: 10.1111/dar.13434
|View full text |Cite|
|
Sign up to set email alerts
|

Social recovery in substance use disorder: A metasynthesis of qualitative studies

Abstract: Issues In substance use disorder, connection to social communities plays a significant role in the recovery process. The aim here has been to identify and synthesise the qualitative research examining the process of social recovery from a first‐person perspective and how social communities assist in this process. Approach Metasynthesis using the following databases: CINAHL, Embase, MEDLINE, PsycINFO, Scopus, SocIndex and Web of Science. The search returned 6913 original articles, of which 18 met the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
(316 reference statements)
2
1
0
1
Order By: Relevance
“…However, a study investigating the 5-year reliability of reported alcohol consumption found that alcohol consumption may actually be more accurately recalled retrospectively compared with presently. 21 Other surveyed-based retrospective studies support the methods of this study and the reliability of retrospective recall of substance use. 22,23 Because of the sensitive nature of questions about relapsing and SUD treatment, it is also possible that our data represent an underreporting of the actual records.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, a study investigating the 5-year reliability of reported alcohol consumption found that alcohol consumption may actually be more accurately recalled retrospectively compared with presently. 21 Other surveyed-based retrospective studies support the methods of this study and the reliability of retrospective recall of substance use. 22,23 Because of the sensitive nature of questions about relapsing and SUD treatment, it is also possible that our data represent an underreporting of the actual records.…”
Section: Discussionsupporting
confidence: 67%
“…Our findings are limited by the retrospective nature of this study, which increases the risk of recall bias from our participants. However, a study investigating the 5-year reliability of reported alcohol consumption found that alcohol consumption may actually be more accurately recalled retrospectively compared with presently 21 . Other surveyed-based retrospective studies support the methods of this study and the reliability of retrospective recall of substance use 22,23 .…”
Section: Discussionsupporting
confidence: 61%
“…Madde kullanım bozukluğunda, olumlu toplumsal bağların iyileşme üzerinde önemli rol oynadığı belirtilmektedir. Arınma sürecindeki bireylerde, düşük damgalanma hissi ve yüksek güvenlik hissi toplumsal aidiyet ile ilişkilendirilmiştir (37). DS grubunda, düşük toplumsal aidiyet, riskli davranışlarda bulunan akranlara sahip olma ve/veya ebeveynlerden yetersiz destek alma gibi ek olumsuz psikososyal faktörlerin maddeyi deneme veya sorunlu kullanım üzerinde daha fazla etkili olabileceği öne sürülmüştür (38).…”
Section: Discussionunclassified
“…This focus is welcomed and highlights the move toward more individualized, tailored, and personalized treatment approaches (2). A personalized treatment approach for SUDs depends on detailed knowledge of how biological, psychological, and social factors impact the severity, trajectory, and recovery of SUDs (3)(4)(5). Thus, targeted efforts are needed to enable personalized treatment approaches for SUD populations with distinct clinical needs (5).…”
Section: Introductionmentioning
confidence: 99%